Early postnatal demoralisation among primiparous women in the community: measurement, prevalence and associated factors. Issue 1 (December 2015) - Bobevski, Irene; Rowe, Heather; Clarke, David; McKenzie, Dean; Fisher, Jane
Abstract Background Demoralisation is a psychological state occurring in stressful life situations where a person feels unable to respond effectively to their circumstances, characterised by feelings of distress, subjective incompetence, helplessness and hopelessness. The period after the birth of a first baby is a time of great changes and disruptions to many aspects of the mother's physical, psychological and social functioning. This can lead to feelings of distress, a sense of incompetence and helplessness. This study aimed to examine: (1) the psychometric properties of the Demoralisation Scale in a community setting; (2) the prevalence of demoralisation symptoms among primiparous women in the community; and (3) factors that are uniquely associated with demoralisation in the early postnatal period. Methods Primiparous women attending community maternal health centres (n = 400) were recruited and administered the study's questionnaires through a telephone interview. Results The Demoralisation Scale was found to be a reliable and valid tool among women in the community who had recently given birth. Higher levels of demoralisation were independently associated with lower confidence on going home from the hospital after birth, lower rating of mother's self-rated global health, more than 3 h of infant crying and fussing in the last 24 h, and a controlling partner, after symptoms of depression and anxiety, and vulnerable personality characteristics were controlled for. Conclusions The relevance of demoralisation to postnatal health practitioners in the community is in helping them to better understand women's experiences and to intervene in a way that is more meaningful and less stigmatising to women.